Learning Media In Early Childhood Education Curriculum In Instilling Religious Character From The Perspective Of The Qur’an - Aziz, Mursal; Napitupulu, Dedi Sahputra; Siregar, Siti Khodizah (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study aims to explore the role of learning media in the Early Childhood Education (ECE) curriculum to instill religious character in children, with the perspective of the Qur’an as a theoretical basis. Along with the importance of early character education, ECE has a crucial role in forming the moral and spiritual foundations of children. Through a literature study approach, this study examines various relevant sources, both from educational literature, learning theories, and interpretations of the Qur’an, to see how learning media can be used effectively in instilling religious values in early childhood. The results of this study indicate that the use of appropriate learning media, such as pictures, videos, stories, and play activities based on the teachings of the Qur’an, can help children understand and internalize religious values. Religious character learning in ECE not only includes teaching religious teachings, but also developing children’s attitudes and behaviors that reflect the values of goodness and virtue according to Islamic teachings. The media used must touch on the cognitive, emotional, and social aspects of children, and be adjusted to their age development. Early childhood education based on religious character can be an effective means to form a generation that is not only intellectually intelligent, but also has good character, noble morals, and is religious. Therefore, the role of learning media in the ECE curriculum is very important in instilling religious values contained in the Qur’an at the stage of early childhood development.